A nomenclatural study on Statice densiflora (Plumbaginaceae) and its linked names - Erben, Matthias; Del Guacchio, Emanuele; Caputo, Paolo (Phytotaxa, 2018)
Four names in Statice, i.e. S. densiflora, S. densiflora var. humilis, S. densiflora var. obtusifolia, and S. secundiramea are typified by employing illustrations or herbarium specimens kept in NAP. Two of these names are basionyms for the accepted combinations Limonium densiflorum and L. secundirameum. The controversial name S. oleifolia, the neglected name S. scolopiana, and the misapplied name S. spathulata sensu Jan are also discussed. Finally, the authors highlight the automatic typification of the illegitimate name S. oxylepis.